2005
DOI: 10.1587/elex.2.501
|View full text |Cite
|
Sign up to set email alerts
|

SAW characteristics of GaN layers with surfaces exposed by dry etching

Abstract: Abstract:We evaluated the possibility of monolithic integration of electron devices and surface acoustic wave (SAW) devices on GaN. We removed top n+ GaN layers of n+ GaN/unintentionally-doped GaN structures by inductively coupled plasma (ICP) etching and fabricated SAW filters on the exposed unintentionally doped GaN layers. We found that the device characteristics are almost the same as those of devices fabricated on as-grown GaN layers, although the surface morphology of GaN layers is degraded due to the IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The present authors previously discussed the characteristics of SAW devices fabricated on GaN layers exposed by dry etching [11], side-gate effects [12], and excitation of SAWs using n + -GaN-based interdigital transducers (IDTs) [13]. Calle et al [14] reported characteristics of SAW filters made of Ni/Au or Pt/Ti/Au-based IDTs fabricated on AlGaN/GaN heterostructures.…”
Section: Saw Filters Composed Of Interdigital Schottky and Ohmic Contmentioning
confidence: 99%
“…The present authors previously discussed the characteristics of SAW devices fabricated on GaN layers exposed by dry etching [11], side-gate effects [12], and excitation of SAWs using n + -GaN-based interdigital transducers (IDTs) [13]. Calle et al [14] reported characteristics of SAW filters made of Ni/Au or Pt/Ti/Au-based IDTs fabricated on AlGaN/GaN heterostructures.…”
Section: Saw Filters Composed Of Interdigital Schottky and Ohmic Contmentioning
confidence: 99%
“…This integration requires the removal [5] or depletion [6], [7] of two-dimensional electron gas (2DEG) in the heterojunction channel in the SAW device region. The presence of the charge conductivity in 2DEG channel can screen the electric field and prohibit the acousto-electric transductions in the interdigital transducers (IDTs).…”
Section: Introductionmentioning
confidence: 99%
“…This integration requires the removal 5 or depletion 6,7 of two-dimensional electron gas ͑2DEG͒ in the heterojunction channel in the SAW device region. The presence of the charge conductivity in 2DEG channel can screen the electric field and prohibit the acoustoelectric transductions in the interdigital transducers ͑IDTs͒.…”
mentioning
confidence: 99%